The mythical Mediterranean sea : crossroads of cultures, people, and civilizations - Ceramella, Nick; Gori, Umberto (Cambridge Scholars Publishing, 2019)
This volume brings together papers presented at the 7th Annual International Conference co-organised by Florence University of the Arts, Italy, and Stony Brook University (SUNY), USA. The contributors explored the many connections that define the Mediterranean Sea as a symbol of tradition and modernity, and examined it as a region capable of congregating, synergizing and transforming cultures. Their writings focus on the relationship between the cultural, social, and historical environment of Mare Nostrum to pinpoint the elements defining its identity. Hence, particular emphasis is placed on the role and relevance of the Mediterranean as the first beacon of multi-ethnicity which may be seen as a symbol of diversity and unity, as well as a model that holds clues to understanding the global merging of cultures. As such, it is a real shame to see that the general interest in this unique and fascinating area has arisen not thanks to such highly positive features, but because, as Pope Francis says, it has become an open-air cemetery where thousands of people keep drowning